Republic of Mozambique : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2005)
This Annual Progress Report reviews Mozambique's Economic and Social Plan for 2004. The report states that in 2004, public sector reforms were continued and consolidated. There was notable growth in social and economic infrastructure. The government was able to honor its budget execution commitments, channelling more resources into sectors prioritized in the Program for the Reduction of Absolute Poverty (PARPA) and keeping budget execution rates within the limits set in the budgetary legislation.